1990
DOI: 10.1093/rheumatology/29.5.325
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF SERUM Vicfflb LIGHT CHAINS IN RHEUMATOID ARTHRITIS AND CORRELATION WITH CD5-POSITIVE -CELLS

Abstract: The presence of V kappa IIIb light chains in the sera of rheumatoid arthritis (RA) patients has been evaluated by an enzyme-linked immunosorbent assay (ELISA). V kappa IIIb light chains have been confirmed to be largely restricted to IgM, and were rarely detected in the IgG fraction of sera. The concentration of total serum V kappa IIIb did not significantly vary with age, nor did it correlate with IgM-rheumatoid factor (RF) titre. Although total serum V kappa IIIb was not significantly increased in RA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found increased percentages of CD5 B cells in RA (fig 4), however, these differences were not significant compared with healthy controls (table 1). The increased frequency of CD5 B cells in RA blood was initially reported by Plater-Zyberk et al, in 1985's and observed by others, 9 15 17 32 but not all reports have confirmed these findings.33 34 These controversial results may be due to a number of reasons, including the wide differences in the epitope density of CD5 on the B cell membrane, patient sampling, drug regime, and the different sensitivities of the methods used. Our study found different epitope density of CD5 on the B cells with three populations of CD5 B cells being observed ( fig 5) Our data showed the levels of CD5 B cells in the PB of patients with RA and other inflammatory arthritides were stable over time (table 2).…”
Section: Discussionmentioning
confidence: 91%
“…We found increased percentages of CD5 B cells in RA (fig 4), however, these differences were not significant compared with healthy controls (table 1). The increased frequency of CD5 B cells in RA blood was initially reported by Plater-Zyberk et al, in 1985's and observed by others, 9 15 17 32 but not all reports have confirmed these findings.33 34 These controversial results may be due to a number of reasons, including the wide differences in the epitope density of CD5 on the B cell membrane, patient sampling, drug regime, and the different sensitivities of the methods used. Our study found different epitope density of CD5 on the B cells with three populations of CD5 B cells being observed ( fig 5) Our data showed the levels of CD5 B cells in the PB of patients with RA and other inflammatory arthritides were stable over time (table 2).…”
Section: Discussionmentioning
confidence: 91%